Analisis Penerapan Digitalisasi Arsip Dokumen Keuangan pada Bagian Umum dan Tata Usaha Balai Besar Pelaksanaan Jalan Nasional - Siti Andriani; Ade Kemala Jaya (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2026)
The development of information technology encourages government agencies to implement digital systems in administrative management, including the filing of financial documents. This study aims to analyze the application of digitization of financial document archives in the General and Administration Section of the South Sumatra National Road Implementation Center, find out the benefits obtained, and identify obstacles faced in its implementation. The research uses a descriptive method with a qualitative approach. Data was obtained through direct observation during internship activities, documentation, internship logbooks, and literature studies. The results of the study show that the digitization of financial document archives is carried out through the stages of document completeness, scanning, digital storage, archive grouping, and document retrieval. The implementation of archive digitization provides benefits in the form of easier document searching, reducing the risk of losing archives, increasing work effectiveness and efficiency, saving storage space, improving data security, and supporting the digital transformation of government agencies. However, there are still several obstacles such as the large volume of documents, the need for high precision in the scanning process, file naming errors, device and system interference, the risk of digital data loss, limited human resources, and the simultaneous management of physical and digital archives. Therefore, it is necessary to improve the quality of digital archive management so that the benefits obtained can be more optimal.